Impact of COVID-19 Lockdown on Air Pollutant Emissions in Port Regions. Scoping Review - Sandro Roberto Mastellari Francisco; Giullia Carvalho Mangas Lopes; Gustavo Duarte Mendes; Nicole Amado Riso; Victória Iglesias Breda; Marcela Gonçalves Leal; Elaine Marcílio Santos; Ana Luiza Cabrera Martimbianco (Epidemiology, Biostatistics and Public Health)
Background: This scoping review, a comprehensive effort to map and synthesize evidence, sheds light on the impacts of the COVID-19 lockdown on air pollutant emissions in port regions.